Fail Path Analysis on Openflow Network Using Floyd-Warshall Algorithm - Ebim Fatur Rohman; Ritzkal Ritzkal; Yuggo Afrianto (Jurnal Mantik, 2020)
Software-Defined Network (SDN) is a new concept used to solve network problems by separating the control plane and data plane in a different device. Communication between the control plane and the data plane uses the Openflow scenario. SDN has several capabilities in many network technology methods and has been implemented, among others, for routing mechanisms. In routing, there are several problems including failure path. When a fail path occurs, the system will look for another shortest path using the Floyd-Warshall algorithm. The Floyd-war shall algorithm will be implemented using the POX controller. The implementation uses a mesh topology on the mininet emulator and pox as a controller. This research method includes analysis consisting of the preparation of hardware and software requirements, and analysis of how the system works, a design consisting of mesh topology, Floyd-war shall algorithm flowchart, propagation testing, throughput, and latency testing, implementation consisting of operating system installation, Mininet, POX, Applying Mesh topology to the Mininet Emulator, and Applying the Floyd-war shall Algorithm to the POX Controller, manually calculating the Floyd-Warshall algorithm on the mesh topology and testing which consists of testing propagation, throughput, and latency. Furthermore, testing with 3 tests is propagation, throughput, and latency. In testing the throughput and latency there are 3 scenarios.